The PROTAC technology in drug development - Zou, Yutian; Ma, Danhui; Wang, Yinyin (Cell biochemistry and function, 2019)
Currently, a new technology termed PROTAC, proteolysis targeting chimera, has been developed for inducing the protein degradation by a targeting molecule. This technology takes advantage of a moiety of targeted protein and a moiety of recognizing E3 ubiquitin ligase and produces a hybrid molecule to specifically knock down a targeted protein. During the first decade, three pedigreed groups worked on the development of this technology. To date, this technology has been extended by different groups, aiming to develop new drugs against different diseases including cancers. This review summarizes the contributions of the groups for the development of PROTAC. Significance of the study This review summarized the development of the PROTAC technology for readers and also presented the author's opinions on the application of the technology in tumor therapy.